Active monitoring of adverse reactions following COVID-19 and other vaccinations: a feasibility study as part of the CoVaKo project - Zeschick, Nikoletta; Warkentin, Lisette; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Hueber, Susann; Sebastiao, Maria (Pilot and Feasibility Studies, 2022)
Background: The Corona-Vakzin-Konsortium project (CoVaKo) analyses the efficacy and safety of COVID-19 vaccines in a real-world setting, as well as breakthrough infections in Bavaria, Germany. A subproject of CoVaKo aims to identify adverse reactions of the COVID-19 vaccine and compare these to adverse reactions of other vaccines in an online survey. In a preceding feasibility study, the study materials were tested for comprehensibility, visual design, and motivation to participate, as well as for their ability to be implemented and carried out in primary care practices and vaccination centres. Methods: We used a mixed-methods research design. First, three focus groups consisting of general population participants were organised to evaluate the study materials and survey. Second, a test roll-out was conducted in vaccination centres and primary care practices that involved implementing and quantitatively evaluating the online survey. Third, interviews were conducted with participating general practitioners and heads of vaccination centres four weeks after the test roll-out. Results: Parts of the information and registration form proved incomprehensible, specifically regarding the recruitment material and/or online survey. For example, headings were misleading given that, relative to other vaccinations, the COVID-19 vaccination was overemphasised in the title. Participants requested additional information regarding the procedure and completion time. Within 31 days, 2199 participants, who received either a COVID-19 vaccination (99%) or at least one of the control vaccinations (1%), registered for the study. Participants (strongly) agreed that the registration process was easy to understand, that the completion time was reasonable, and that the technical setup was straightforward. Physicians and heads of the vaccination centres perceived the study as easy to integrate into their workflow. The majority expressed willingness to participate in the main study. Conclusions: Our study indicated that identifying and documenting adverse reactions following vaccinations using an online survey is feasible. Testing materials and surveys provided valuable insight, enabling subsequent improvements. Participation from health professionals proved essential in ensuring the practicality of procedures. Lastly, adapting the study’s organisation to external fluctuating structures and requirements confirmed necessary for a successful implementation, especially due to dynamic changes in the nation’s COVID-19 vaccination strategies. Trial registration: The trial was retrospectively registered at the “Deutsches Register Klinischer Studien” (DRKS-ID: DRKS00025881) on Oct 14, 2021.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Adverse reactions; COVID-19; General practitioners; Healthcare staff; Online survey; Vaccination; Vaccination centres

Asynchronous, digital teaching in times of COVID-19: a teaching example from general practice - van der Keylen, Piet; Lippert, Nikoletta; Kunisch, Raphael; Kühlein, Thomas; Roos, Marco (GMS Journal for Medical Education, 2020)
Background: The SARS-CoV-2 pandemic had a strong impact on academic teaching and could change it sustainably. Ad hoc digitization of teaching had to be carried out.
CRIS-Team WoS Importer:2021-01-08

Auswirkungen eines Wahlfachs zur evidenzbasierten klinischen Entscheidungsfindung auf die Kompetenzen und Einstellungen von Medizinstudierenden: Eine Pilotstudie - Lippert, Nikoletta; Frank, Luca; Schnitzius, Kathrin; Stubner, Birgit Maria; Kühlein, Thomas; Roos, Marco; van der Keylen, Piet (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2021)
Background: Evidence-based medicine (EbM) as a teaching subject is increasingly taken into account in the Master Plan 2020. To date, neither theoretical requirements nor practical applications of EbM have been consistently implemented in the clinical curriculum. To fill this gap, a digital and tutor-based EbM course has been developed. The aim is to identify the student characteristics (statistical competence, Need for Cognition (NFC), work and experience patterns (AVEM), diagnostic uncertainty) of the first cohort in order to ensure successful course implementation and to prepare future doctors for their role as mediators of health literacy using EbM methods. Methods: The long-term study started in the summer term 2019 with 10 medical students during their clinical training. The measurements were conducted before (t0) and after course attendance (t1). Socio-demographic variables were taken at t0, the Quick Risk Test, PRU questionnaire, the NFC scale and the AVEM were collected at t0 and t1. Results: Half of the students started their doctoral thesis before attending the course. The first test results of the Quick Risk Test (t0) were between 50 % and 90 % and at t1 between 60 % and 100 %. The students showed high scores on the NFC scale (X¯ = 4.6, SD = 0.52, Δ X¯ t0 - t1 = 0.1) and medium scores on the Perfectionism scale (X¯ = 3.8, SD = 0.51, Δ X¯ t0 - t1 = 0.1), Resignation Tendency (X¯ = 3.8, SD = 1.17, Δ X¯ t0 - t1 = 0.1) and on the scale Aggressive Problem Solving (X¯ = 3.9, SD = 1.06, Δ X¯ t0 - t1 = 0.2). They achieved high levels of Anxiety Due to Diagnostic Uncertainty (X¯ = 4.8, SD = 0.69, Δ X¯ t0 - t1 = 0.4) and on the scale Concern about Poor Outcomes (X¯ = 3.9, SD = 1.54, Δ X¯ t0 - t1 = 0.6). The scale Restraint in Disclosing Uncertainty to Patients was more pronounced than the scale Restraint in Disclosing Errors to Physicians (X¯ = 3.5, SD = 0.93, Δ X¯ t0 - t1 = -0.3 compared to X¯ = 2.3, SD = 1.20, Δ X¯ t0 - t1 = 0.1). Discussion: Statistical competence improved with course attendance, with only one student being able to correctly answer all items at t1. NFC and AVEM were strongly expressed and were not very sensitive to change in the sample. The greatest changes were observed on the scales of concern about poor results and fear of diagnostic uncertainty, both of which decreased with course participation. Conclusion: In the long term, the development of a new measuring instrument to assess EbM competencies instead of the Quick Risk Test is conceivable. The longitudinal design will also enable us to make causal interpretations and to track changes in students’ competence feelings, behaviour and attitudes.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Decision-making; Evidence-based medicine; Health literacy; Physicians’ reaction to uncertainty; Quick Risk Test

Bedeutung schulischer Merkmale für das Wohlbefinden SchülerInnen der Primarstufe - Hofmann, Florian; Bonitz, Melanie; Lippert, Nikoletta; Gläser-Zikuda, Michaela (AEPF-Tagung "Empirisch pädagogische Forschung in inklusiven Zeiten - Professionalisierung, Konzeptualisierung, Systementwicklung", 2016)
Ziele oder Fragestellungen im Kontext des theoretischen Rahmens und Forschungsstandes Das Verhältnis von Grundschüler/innen zur Schule ist generell positiv, aber auch durch einen Rückgang der Lernfreude (Helmke, 1993) bereits in den ersten Schuljahren gekennzeichnet. Ursächlich hierfür gelten soziale Bezugsnormorientierung, Leistungsdruck und schulische Selektionsprozesse (Kramer, Helsper, Thiersch & Ziems, 2009). Die vorliegende Studie untersucht daher individuelle und kontextuelle Bedingungen des Wohlbefindens von Grundschüler/innen. Entsprechend der Mehrkomponentenstruktur von Hascher (2004) setzt sich Wohlbefinden aus psychischen und physischen Komponenten zusammen. Positive Emotionen und Kognitionen, als auch die Abwesenheit von Beschwerden, negativen Emotionen und Kognitionen sind für Wohlbefinden konstitutiv. In der zu präsentierenden Studie wurde untersucht, wie psychisches sowie physisches Wohlbefinden in der Primarstufe ausgeprägt sind und welche Zusammenhänge mit zentralen Merkmalen schulischen Lernens (Unterrichtsqualität, Lehrerverhalten) bestehen. Methodik Die Daten von insg. 404 Schüler/innen der dritten Grundschulklasse bzw. der Primarstufe an Gemeinschaftsschulen an insgesamt 13 Schulen eines dt. Bundeslandes wurden mittels Fragebogen erhoben. Die Schüler/innen waren durchschnittlich 9 Jahre alt (SD = .65), 46,8 % waren weiblich. Die verwendeten Skalen stammen größtenteils aus standardisierten Instrumenten, wurden jedoch auf die Befragungsbedingungen von Grundschüler/innen angepasst. Folgende Konstrukte wurden erfasst: Psych. Wohlbefinden (Item-Beispiel: „Ich fühle mich in meiner Schule wohl“); phys. Wohlbefinden („Ich hatte schon Bauchschmerzen wegen der Schule“; a = .70); Schülerorientierung („Mein/e Klassenlehrer/in behandelt mich gerecht“; a = .84); Klarheit des Unterrichts („Ich weiß, was ich im Unterricht tun soll“; a = .69), Zufriedenheit mit der schul. Lernsituation („In der Schule zu lernen, macht mir Freude“; a = .70); Unterstützung der Eltern bei den Hausaufgaben (a = .69) sowie die Schulnoten in Deutsch und Mathematik. Ergebnisse bzw. Schlussfolgerungen Erste Ergebnisse zeigen, dass das psychische Wohlbefinden recht hoch mit der Schülerorientierung (r = .60; p = .000) und der Zufriedenheit der Schüler/innen mit der Lernsituation (r = .57; p = .000) sowie moderat mit der Klarheit des Unterrichts (r = .41; p = .000) korreliert. Weitere signifikante, jedoch schwächere Zusammenhänge liegen vor. Zudem werden derzeit vertiefte Analysen, welche die Bedeutung spezifischer Programme (z.B. Individualisierung im Unterricht, Formen der alternativen Leistungsbeurteilung) an den Schulen berücksichtigen, durchgeführt. Im Vortrag werden Design und weitere Ergebnisse der deskriptiven sowie inferenzstatistischen Analysen vorgestellt. Zentrale Befunde werden in Hinblick auf die Bedeutung des psychischen und physischen Wohlbefindens im Grundschulalter diskutiert. Insbesondere werden Fragen der Schul- und Unterrichtsentwicklung sowie der Professionalisierung von Lehrkräften fokussiert. Zusammenfassung für das Programm Das Verhältnis von Grundschüler/innen zur Schule ist generell positiv, aber auch durch einen Rückgang der Lernfreude (Helmke, 1993) bereits in den ersten Schuljahren gekennzeichnet. Ursächlich hierfür gelten soziale Bezugsnormorientierung, Leistungsdruck und schulische Selektionsprozesse (Kramer, Helsper, Thiersch & Ziems, 2009). Die vorliegende Studie untersucht daher individuelle und kontextuelle Bedingungen des psychischen und physischen Wohlbefindens von Grundschüler/innen in Anlehung an Hascher (2004). Insbesondere wird untersucht, wie psychisches sowie physisches Wohlbefinden ausgeprägt sind und wie sie mit Merkmalen schulischen Lernens (Unterrichtsqualität, Lehrerverhalten, Noten) zusammenhängen. Insg. 404 Schüler/innen der dritten Grundschulklasse bzw. der Primarstufe an Gemeinschaftsschulen aus 13 Schulen wurden befragt. Die Schüler/innen waren durchschnittlich 9 Jahre alt, 46,8 % weiblich. Die verwendeten Skalen beruhen auf standardisierten Instrumenten, wurden jedoch für die Grundschüler/innen angepasst. Erste Ergebnisse zeigen, dass psychisches Wohlbefinden hoch mit der Schülerorientierung (r = .60; p = .000) und der Zufriedenheit mit der Lernsituation (r = .57; p = .000) sowie moderat mit der Klarheit des Unterrichts (r = .41; p = .000) korreliert. Design und weitere Ergebnisse der deskriptiven sowie inferenzstatistischen Analysen werden vorgestellt und mit Blick auf die Bedeutung des psychischen und physischen Wohlbefindens im Grundschulalter diskutiert. <br
Keywords: Schulisches Wohlbefinden; Emotionen; Schulangst; Grundschule; Schulklima

Controlling Prescribing through “Preferred Drug” Targets—The Bavarian Experience - Gollnick, Julia; Zeschick, Nikoletta; Muth, Julia; Hörbrand, Franziska; Behnke, Kerstin; Killian, Peter; Sebastiao, Maria; Kühlein, Thomas; Donner-Banzhoff, Norbert (International Journal of Environmental Research and Public Health, 2024)
Background: The rising costs of drugs are putting health care systems under pressure. We report on the Bavarian Drug Agreement, which employs prescribing targets for preferred and generic drugs in ambulatory care. Under this agreement, providers are regularly profiled with individual feedback but also possible sanctions. We investigated the degree to which targets were being met (or not) and why failure occurred. Methods: We analysed prescribing data aggregated by practice for the quarter 1/2018. We chose eight specialisation groups and analysed their drug targets with a high prescribing volume, widely missed drug targets (<90%), and drugs preventing drug target achievement. Characterisation of drug targets and preventing drugs was undertaken. Results: Drug targets with a high prescribing volume are mostly achieved, while highly missed drug targets mostly do not affect the main indication area of the specialisation groups considered. Generic drug targets seem to be more easily achieved than recommended drug targets. Paediatrics accounts for the largest number of missed drug targets. Conclusions: The Bavarian tool implemented uses the prescribing volume (DDD) and price components to evaluate the prescription behaviour of physicians. Well-established drugs with demonstrated effectiveness, safety, and lower costs are preferred. Nevertheless, me-too drugs, combination drugs, costly innovations with unclear value, and drugs with application methods of variable convenience challenge the drug prescribers and are reasons for missed drug targets.
CRIS-Team Scopus Importer:2024-10-11
Keywords: ambulatory care/economics; budgets; cost control/trends; drug prescriptions; drug therapy/economics; drug therapy/trends

Innovative Schulen im Kontext von Schulentwicklung – was zeichnet sie aus? - Gläser-Zikuda, Michaela; Stephan, Melanie; Wenke, Fridolin; Lippert, Nikoletta (AEPF 2015, 2015)

One year of general practice during the COVID-19 pandemic - presentation and evaluation of digital medical education - van der Keylen, Piet; Zeschick, Nikoletta; Langer, Amelie; Kühlein, Thomas; Roos, Marco (GMS Journal for Medical Education, 2022)
Background and teaching situation: The SARS-CoV-2 pandemic had a substantial didactic impact on medical teaching. In Erlangen, the lecture "General Practice" was offered asynchronously and digitally in an inverted-classroom concept. Contents were available via a learning platform. The lecture was presented using annotated videos, consolidation materials and control questions. A forum encouraged for discussions and feedback and collected in-depth aspects for a case-based video consultation. The aim of this work is to evaluate and critically examine the digital teaching concept during the SARS-CoV-2 pandemic.
CRIS-Team WoS Importer:2022-09-09

Patient-reported reactogenicity and safety of COVID-19 vaccinations vs. comparator vaccinations: a comparative observational cohort study - Werner, Felix; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Sebastião, Maria; Hueber, Susann; Warkentin, Lisette (BMC Medicine, 2023)
Background: In the course of the SARS-CoV-2 pandemic, multiple vaccines were developed. Little was known about reactogenicity and safety in comparison to established vaccines, e.g. influenza, pneumococcus, or herpes zoster. Therefore, the present study aimed to compare self-reported side effects in persons vaccinated against SARS-CoV-2 with the incidence of side effects in persons receiving one of the established vaccines. Methods: A longitudinal observational study was conducted over a total of 124 days using web-based surveys. Persons receiving either a vaccination against SARS-CoV-2 or one of the established vaccines (comparator group) were included. In the first questionnaire (short-term survey), 2 weeks after vaccination, mainly local and systemic complaints were evaluated. The long-term survey (42 days after vaccination) and follow-up survey (124 weeks after vaccination) focused on medical consultations for any reason. Multivariate analyses were conducted to determine the influence of the vaccine type (SARS-CoV-2 vs. comparator) and demographic factors. Results: In total, data from 16,636 participants were included. Self-reported reactogenicity was lowest in the comparator group (53.2%) and highest in the ChAdOx1 group (85.3%). Local reactions were reported most frequently after mRNA-1273 (73.9%) and systemic reactions mainly after vector-based vaccines (79.8%). Almost all SARS-CoV-2 vaccines showed increased odds of reporting local or systemic reactions. Approximately equal proportions of participants reported medical consultations. None in the comparator group suspected a link to vaccination, while this was true for just over one in 10 in the mRNA-1273 group. The multivariate analysis showed that people with SARS-CoV-2 vaccination were not more likely to report medical consultations; patients who had received a regimen with at least one ChAdOx1 were even less likely to report medical consultations. Younger age, female gender and higher comorbidity were mostly associated with higher odds of medical consultations. Conclusion: The rate of adverse reactions after established vaccinations was roughly comparable to previous studies. Two weeks after vaccination, participants in the SARS-CoV-2 vaccination group reported more local and systemic local reactions than participants in the comparator group. In the further course, however, there were no higher odds of medical consultations in either of the two groups. Thus, altogether, we assume comparable safety. Trial registration: DRKS-ID DRKS00025881 and DRKS-ID DRKS00025373.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Adverse drug reaction; COVID-19; Medical consultation; Observational study; Reactogenicity; SARS-CoV-2; Survey; Vaccine

Physicians’ assessment of the Bavarian drug-expenditure control system: a qualitative study - Zeschick, Nikoletta; Gollnick, Julia; Muth, Julia; Hörbrand, Franziska; Killian, Peter; Donner-Banzhoff, Norbert; Kühlein, Thomas; Sebastiao, Maria (BMC Health Services Research, 2023)
Background: In 2014 a new system for drug expenditures, the Wirkstoffvereinbarung (WSV, English: Active substance agreement) was implemented in Bavaria. In pre-defined indication groups, economic prescription of medications shall be enabled based on the selection, quantity, and proportion of an individual drug. Ambulatory care physicians receive quarterly trend reports on their prescribing behavior. This study examines physicians’ perceptions of the WSV. Methods: Qualitative interviews (n = 20) and seven focus groups (n = 36) were conducted with ambulatory care physicians (e.g. general practitioners, cardiologists, pulmonologists). The methodology followed Qualitative Content Analysis. Results: Physicians generally accepted the necessity of prescribing economically. The majority of them rated the WSV positively and better than the previous system. As an improvement, they especially named timely feedback in form of easily understandable trend reports, encouraging self-reflection as well as allowing early control options. Problems perceived were drug discount contracts that were strongly criticized as leading to patients mixing up medications. Some perceived constraints of therapeutic freedom. Conclusions: The implementation of the WSV is mostly viewed positively by physicians. The restrictions of therapeutic freedom partially perceived might be met by improved information on the reasons why some drugs are rated as less economical than others. Trial registration number: Main ID: DRKS00019820 (German Register of Clinical Studies and World Health Organization).
CRIS-Team Scopus Importer:2023-09-15
Keywords: Active substance agreement; Drug costs; Drug prescriptions; Economic efficiency; Wirkstoffvereinbarung

Prescribing behavior of Bavarian general practitioners at the inpatient-outpatient interface within the context of the Bavarian active substance agreement-qualitative results of the WirtMed Study - Zeschick, Nikoletta; Gollnick, Julia; Muth, Julia; Hoerbrand, Franziska; Killian, Peter; Krombholz, Wolfgang; Donner-Banzhoff, Norbert; Kühlein, Thomas; Sebastiao, Maria (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2022)
Background and objectives In 2014, the Association of Statutory Health Insurance Physicians of Bavaria introduced the active substance agreement (WSV) for the transparent control of pharmaceutical expenditure within the framework of the efficiency principle (</n> 12 of the Fifth Book of the German Social Code [SGB V]). It replaced the prescribing target scheme. Regarding the role of the WSV, the article presents the reasons of the general practitioners (GPs) for or against a further prescription of drugs from the hospital. Materials and methods In a qualitative study design, individual interviews (n = 18) and two focus groups (n = 10) were conducted with Bavarian GPs between November 2019 and March 2020 and evaluated according to qualitative content analysis. Results With the introduction of the WSV, recourse concerns decreased for GPs overall. Patient-oriented care and the professional correctness of therapy decisions are of great importance in prescribing, ahead of cost-effectiveness. Economic challenges arise with discharge medication, especially with the lead substance target of oral anticoagulants, the generic targets for antidiabetics, and for therapeutics for the cardiovascular system. Generally criticized are drug discount contracts, which often lead to drug changes after hospital discharge. There are individual reports of a "predominance" of hospital physicians when prescribing, which is contrary to their own economic actions as GPs. According to the GPs, there is a lack of cross-sectoral cost responsibility. Conclusions In the view of GPs, a smooth interface transition is not yet available in the outpatient sector despite a framework agreement on discharge management and the new control system of the WSV. An economical supply of drugs continues to require political discussion across sectors, but also across federal states.
CRIS-Team WoS Importer:2022-07-29

Reactogenicity after heterologous and homologous COVID-19 prime-boost vaccination regimens: descriptive interim results of a comparative observational cohort study - Warkentin, Lisette; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Gall, Christine; Sebastiao, Maria; Hueber, Susann (BMC Infectious Diseases, 2022)
Background Due to safety signals after vaccination with COVID-19 vector vaccines, several states recommended to complete the primary immunization series in individuals having received one dose of ChAdOx1 (AstraZeneca) with an mRNA vaccine. However, data on safety and reactogenicity of this heterologous regimen are still scarce. The aim of this study was therefore to compare the reactogenicity and the frequency of medical consultations after boost vaccination in a heterologous regimen with ChAdOx1 and mRNA-vaccines (BNT162b2, BioNTech/Pfizer or mRNA-1273, Moderna) to homologous regimens with ChAdOx1 or mRNA-vaccines, respectively. Methods In an observational cohort study reactogenicity and safety were assessed 14-19 days (short-term) and 40 to 56 days (long-term) after the boost vaccination using web-based surveys. In the short-term survey solicited and unsolicited reactions were assessed, while the long-term survey focussed on health problems leading to medical consultation after the vaccination, including those that were not suspected to be vaccine-related. Results In total, 9146 participants completed at least one of the surveys (ChAdOx1/ChAdOx1: n = 552, ChAdOx1/mRNA: n = 2382, mRNA/mRNA: n = 6212). In the short-term survey, 86% with ChAdOx1/mRNA regimen reported at least one reaction, in the ChAdOx1/ChAdOx1 and mRNA/mRNA cohorts 58% and 76%, respectively (age and sex adjusted p < 0.0001). In the long-term survey, comparable proportions of individuals reported medical consultation (ChAdOx1/ChAdOx1 vs. ChAdOx1/mRNA vs. mRNA/mRNA: 15% vs. 18% vs. 16%, age and sex adjusted p = 0.398). Female gender was associated with a higher reactogenicity and more medical consultations. Younger age was associated with a higher reactogenicity, whereas elderly people reported more medical consultations. Conclusion Although the short-term reactogenicity was higher with the heterologous regimen than with the homologous regimens, other factors such as higher efficacy and limited resources during the pandemic may prevail in recommending specific regimens.
CRIS-Team WoS Importer:2022-06-17

Reactogenicity and safety of COVID-19 primary immunisation and booster vaccination regimens: a comparative observational cohort study - Warkentin, Lisette; Werner, Felix; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Sebastiao, Maria; Hueber, Susann (BMC Medicine, 2023)
Background: Since the beginning of the COVID-19 vaccination campaigns, recommendations regarding the vaccination have been very dynamic. Although the safety and efficacy of different vaccines have been analysed, data were scarce for vaccine regimens combining different vaccines. We therefore aimed to evaluate and compare the perceived reactogenicity and need for medical consultation after the most frequently applied homologous and heterologous COVID-19 vaccination regimens. Methods: In an observational cohort study, reactogenicity and safety were assessed within a maximum follow-up time of 124 days using web-based surveys. Reactogenicity was assessed for different vaccination regimens 2 weeks after a vaccination (short-term survey). The following surveys, long-term and follow-up surveys, focused on the utilisation of medical services, including those that were not suspected to be vaccine-related. Results: Data of 17,269 participants were analysed. The least local reactions were seen after a ChAdOx1 − ChAdOx1 regimen (32.6%, 95% CI [28.2, 37.2]) and the most after the first dose with mRNA-1273 (73.9%, 95% CI [70.5, 77.2]). Systemic reactions were least frequent in participants with a BNT162b2 booster after a homologous primary immunisation with ChAdOx1 (42.9%, 95% CI [32.1, 54.1]) and most frequent after a ChAdOx1 − mRNA-1273 (85.5%, 95% CI [82.9, 87.8]) and mRNA-1273/mRNA-1273 regimen (85.1%, 95% CI [83.2, 87.0]). In the short-term survey, the most common consequences were medication intake and sick leave (after local reactions 0% to 9.9%; after systemic reactions 4.5% to 37.9%). In the long-term and follow-up surveys, between 8.2 and 30.9% of participants reported consulting a doctor and between 0% and 5.4% seeking hospital care. The regression analyses 124 days after the first and after the third dose showed that the odds for reporting medical consultation were comparable between the vaccination regimens. Conclusions: Our analysis revealed differences in reactogenicity between the COVID-19 vaccines and vaccination regimens in Germany. The lowest reactogenicity as reported by participants was seen with BNT162b2, especially in homologous vaccination regimens. However, in all vaccination regimens reactogenicity rarely led to medical consultations. Small differences in seeking any medical consultation after 6 weeks diminished during the follow-up period. In the end, none of the vaccination regimens was associated with a higher risk for medical consultation. Trial registration: DRKS DRKS00025881 (https://drks.de/search/de/trial/DRKS00025373 ). Registered on 14 October 2021. DRKS DRKS00025373 (https://drks.de/search/de/trial/DRKS00025881 ). Registered on 21 May 2021. Registered retrospectively.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Adverse drug reaction; COVID-19; Medical consultation; Observational study; Reactogenicity; Survey; Vaccines

Surveillance of drug prescribing: why outliers miss their targets – a qualitative study - Gollnick, Julia; Zeschick, Nikoletta; Hörbrand, Franziska; Killian, Peter; Sebastiao, Maria; Kühlein, Thomas; Donner-Banzhoff, Norbert (BMC Health Services Research, 2025)
Background: Rising costs are a challenge for healthcare systems. To keep expenditure for drugs under control, in many healthcare systems, drug prescribing is continuously monitored. The Bavarian Drug Agreement (German: Wirkstoffvereinbarung or WSV) for the ambulatory sector in Bavaria (the federal state of Germany) was developed for this purpose. Physicians must reach defined drug target quotas for prescribing generic drugs and certain recommended drugs specified and measured with defined daily doses (DDD). A subgroup of physicians, known as outliers, may miss their drug targets. The objective of this qualitative study was to understand the reasons physicians miss their targets. Methods: We identified outliers based on drug prescribing data from the association of statutory health insurance (SHI)-accredited physicians (KV). Outliers were invited to participate in semi-structured interviews. Results: Out of 401 outliers thus identified n = 26 physicians were interviewed. Their prescribing behaviours are affected by competing demands regarding drug decisions, such as saving staff time, costs, and discussions with patients. Often, their freedom to prescribe is limited by previous prescribers. Ease of administration of drugs not recommended also plays a role. Uncritical enthusiasm regarding the effectiveness and safety of drugs with recommendations, often reinforced by pharmaceutical marketing, leads to missed targets. Some physicians have coping strategies to avoid becoming outliers. Conclusions: Investigating physicians not meeting their targets helps us understand beliefs and barriers for appropriate drug prescribing. Based on these kinds of findings, surveillance procedures can be improved, and physicians can receive support to meet targets in the future. Trial registration: This trial has been registered in the German Register of Clinical Trials (DRKS: DRKS00016161; registration date 07. December 2018).
CRIS-Team Scopus Importer:2025-01-31
Keywords: Clinical decision-making; Drug costs; Drug prescriptions; Qualitative research; Quality of health care/economics

Treatment thresholds and minimal clinically important effect sizes of antiosteoporotic medication–Survey among physicians and lay persons in Germany - van der Keylen, Piet; Zeschick, Nikoletta; Schlenz, Anna; Kühlein, Thomas (PLoS ONE, 2022)
Background Patient decisions to take preventative treatments for osteoporosis depend on their perceptions of fracture risk, medication effect sizes (ES) of benefits and harms. However, physicians and lay persons may have differing perceptions of risks and medication efficacy. Both tend to overestimate medication benefits. This study surveyed at what risk physicians would prescribe and lay persons would be willing to take bisphosphonates, the minimum ES both groups do demand and the physicians estimates of the actual benefit of bisphosphonates. Design Cross-sectional online questionnaire survey. Methods Respondents were confronted with a case vignette with an osteoporotic patient (10-year femoral fracture risk: 32%). They were asked at what threshold of 10-year-risk of femoral neck fracture they would prescribe or take a drug. They were asked for the minimum ES (absolute risk reduction, ARR) they demand from bisphosphonates to prescribe or take them. Physicians were asked to provide their estimate of the actual ARR of bisphosphonates. Results 114 physicians and 140 lay persons answered (convenience sample/snowball distribution). The 10-year-risk threshold of lay persons (Mdnlay = 60%) willing to take medication was twice as high as the physicians’ threshold (Mdnphy = 30%) to prescribe it (p < .001). The median minimum ARR physicians demanded for bisphosphonates prescription was 17%, whereas lay persons demanded 22% (p < .001). Physicians estimated the actual ARR of bisphosphonates to be 12%. This estimated effect size was below their own minimum threshold for prescription. Conclusions Lay persons tolerate a higher fracture risk and demand a larger benefit of antiosteoporotic medication for fracture prevention than physicians. Physicians demand higher minimum benefits than their own estimates which in turn are above the benefit evidence suggests. Physicians should be more familiar with ES of antiosteoporotic drugs concerning patient outcomes and actively advise lay persons before preventive treatment decisions are taken.
CRIS-Team Scopus Importer:2022-09-02

Wohlbefinden von Grundschüler/innen – zur Bedeutung schulischer und individueller Determinanten - Gläser-Zikuda, Michaela; Hofmann, Florian; Stephan, Melanie; Lippert, Nikoletta (Emotionen und Emotionsregulation in der Schule und Hochschule, 2018)

Wohlbefinden von Schüler/innen der Sekundarstufe – individuelle, soziokulturelle und unterrichtliche Aspekte - Hofmann, Florian; Stephan, Melanie; Lippert, Nikoletta; Gläser-Zikuda, Michaela (AEPF 2017, 2017)

Wohlbefinden von Sekundarschüler/innen an innovativen Schulen - Hofmann, Florian; Bonitz, Melanie; Lippert, Nikoletta; Gläser-Zikuda, Michaela (Durch Bildung gesellschaftliche Herausforderungen meistern, 2017)
Verständnis und Wahrnehmung von Innovation hängen von der Sichtbarkeit von Neuerungen, den Normen der jeweiligen Domäne, vom sozialen Umfeld und den Individuen ab (Reinmann, 2005). Innovation in der Schule bezogen auf verschiedene Ebenen, Inhalte, die Akteure und Prozesse ist ein zentrales Merkmal von Schulentwicklung (Holtappels, 2013), die häufig auf die Erhöhung der Unterrichtsqualität und des Schulklimas, speziell des Wohlbefindens (Hascher, 2004) der Akteure abzielt. Speziell in der Sekundarstufe, bedingt durch schulische Selektionsprozesse (Kramer, Helsper, Thiersch & Ziems, 2009), wird häufig ein Absinken des Wohlbefindens von Schüler/innen beobachtet. Daher wird der Frage nachgegangen, welche individuellen, sozialen und schulische Faktoren sich als Prädiktoren für das psychische und physische Wohlbefinden identifizieren lassen. Insbesondere interessiert, ob das Wohlbefinden von Schüler/innen sowie die Unterrichtsqualität im Vergleich zu anderen Schulen an innovativen Schulen höher ausgeprägt sind. Die Stichprobe umfasst 1.077 Schüler/innen der siebten bis neunten Klassenstufe aus 14 Sekundarschulen aus einem deutschen Bundesland. Alle Schulen sind in verschiedenen Schulnetzwerken aktiv und einige sind mehrfache Preisträger. Das Durchschnittsalter der Schüler/innen beträgt 14 Jahre (SD = 2.07), 50% davon sind weiblich. Die eingesetzten Skalen der querschnittlich angelegten Befragungsstudie, die im Schuljahr 2014/2015 stattfand, basieren überwiegend auf standardisierten Instrumenten. Das Wohlbefinden der Schüler/innen wurde mit zwei Skalen (Hascher, 2004) erhoben: Psychologisches Wohlbefinden/Schulischer Selbstwert (Beispielitem: „Ich habe keine Probleme die Anforderungen der Schule zu bewältigen“; alpha = .80) und physisches Wohlbefinden/Körperliche Beschwerden (Beispielitem: „In den letzten Wochen hatte ich Bauchschmerzen wegen der Schule“; a = .80). Eine Vielzahl an weiteren Konstrukten auf individueller und kontextueller Ebene wurde erhoben. Auf der individuellen Ebene wurde beispielsweise Lernfreude (Beispielitem: „Ich freue mich oft richtig auf den Unterricht;  a = .77) und Prüfungsangst (Beispielitem: „Ich bin sehr nervös“; a = .85) erfasst. Das soziale Umfeld wurde u.a. über die Fürsorglichkeit der Lehrkräfte (Beispielitem: „Unsere Lehrer kümmern sich um unsere Probleme“; a = .88) und die elterliche Unterstützung (Beispielitem: „Meine Eltern helfen mir beim Lernen“; a = .84) gemessen. Zudem wurde die Schul- und Unterrichtsqualität beispielsweise anhand der Skala schülerorientierter Unterricht (Beispielitem: „Sie/Er erklärt den Unterrichtsstoff verständlich“; a = .89) gemessen. Die interne Konsistenz aller Skalen ist mit Werten zwischen a = .71 und .94. zufriedenstellend bis sehr gut Die Korrelationsanalysen zeigen beispielsweise moderate Zusammenhänge zwischen dem psychischen Wohlbefinden und individuellen Faktoren (z.B. Schulleistung r = .44; p = .001 und Lernfreude r = .35; p = .001) und den Faktoren der Schul- und Unterrichtsqualität (z.B. schülerorientierter Unterricht r = .35; p = .001). Physisches Wohlbefinden/körperliche Beschwerden korrelieren moderat mit dem Unterrichtsdruck (r = .36; p = .001) und der Prüfungsangst (r = .47; p = .001). Die multiple Regressionsanalyse belegt, dass die schulische Selbstwirksamkeitserwartung (beta = .39; p = .001), schulische Herausforderung (beta =.23; p = .001) und Schulleistung (beta =.25; p = .001) Prädiktoren für das psychische Wohlbefinden sind (erklärte Varianz 41 %), während Prüfungsangst (beta =.38; p = .001), Identifikation mit der Schule (beta =.14; p = .01) und Unterrichtsdruck (beta =.14; p = .01) das physische Wohlbefinden (erklärte Varianz 25 %) vorhersagen. Bezüglich des schulischen Wohlbefindens besteht kein signifikanter Unterschied zwischen innovativen und weniger innovativen Schulen. An innovativen Schulen ist allerdings erwartungsgemäß ein höheres Niveau an intrinsischer Motivation (t = 4.54; p = .000), ein höheres Gemeinschafts- (t = 3.81; p = .000) und Selbstbestimmungserleben (t = 2.52; p = .012) und ein geringerer Unterrichtsdruck (t = 2.10; p = .037) zu beobachten. Zentrale Befunde der Studie werden präsentiert und im Hinblick auf die Bedeutung innovativer Schulen für die Förderung von Wohlbefinden diskutiert. Methodische Limitationen wie Implikationen der Studie werden adressier
Keywords: Bildung im Sekundarbereich; Motivation und Emotion; Schulentwicklung; Wohlbefinden; Schüler; Innovative Schulen: Wohlbefinden von Sekundarschüler/innen

Wohlbefinden von Sekundarschüler/innen - individuelle, soziodemographische und schulische Bedingungen. - Hofmann, Florian; Bonitz, Melanie; Lippert, Nikoletta; Gläser-Zikuda, Michaela (Educational Research and Governance, 2017)
Ziele oder Fragestellungen im Kontext des theoretischen Rahmens und Forschungsstandes Der Schule kommt eine wichtige Rolle hinsichtlich der Unterstützung der Bildungsprozesse von Schüler/innen zu. Sie sollte daher auch ein Ort sein, an dem sich diese gerne aufhalten und wohl fühlen. Speziell in der Sekundarstufe, nicht zuletzt auch bedingt durch schulische Selektionsprozesse, wird aber häufig ein Absinken des Wohlbefindens sowie eine vermehrte negative Einstellung den Lehrpersonen gegenüber beobachtet (Bergmann & Eder, 1995). Daneben spielen auch die Erwartungen der Eltern sowie deren Unterstützung in schulischen Belangen eine wesentliche Rolle (Stecher, 2000). In der zu präsentierenden Studie wird daher untersucht, wie psychisches sowie physisches Wohlbefinden ausgeprägt sind und wie sie mit verschiedenen individuellen (u. a. Gender, Schulleistung), soziodemographischen (u. a. Familiensprache, elterliche Unterstützung) und schulischen Aspekten (Lehrerverhalten, Unterricht) zusammenhängen.  Methodik Die Stichprobe der querschnittlich angelegten Studie umfasst 1.077 Schüler/innen der 5. bis 9. Klassenstufe aus 14 Sekundarschulen eines Bundeslandes (Durchschnittsalter 14 Jahre; SD = 2.07; 50% weiblich). Es kamen überwiegend standardisierte Instrumente zum Einsatz. Das schulische Wohlbefinden der Schüler/innen wurde angelehnt an Hascher (2004) erhoben. Die faktorenanalytische Untersuchung weist eine Sieben-Faktoren-Lösung mit einer Varianzaufklärung von 67 % aus. Neben dem Wohlbefinden wurde unter anderem die Unterrichtsqualität (z. B. schülerorientierte Unterrichtsgestaltung), das Lehrerverhalten (z. B. Wertschätzung gegenüber den Schüler/innen) und Aspekte des Schulklimas (z. B. Klassengemeinschaft) erfasst (fünfstufige Skala, höchste Ausprägung 5). Auch die Unterstützung der Eltern, die Schulleistung sowie soziodemographische Variablen wurden erhoben. Die interne Konsistenz aller Skalen ist mit Werten zwischen α = .67 und α = .91 zufriedenstellend bis sehr gut.  Ergebnisse bzw. Schlussfolgerungen Es zeigt sich, dass insgesamt ein mittleres bis hohes schulisches Wohlbefinden in der Stichprobe vorliegt. Allerdings variieren die Werte der Teilkomponenten deutlich: So plagen die Schüler/innen zwar selten körperliche Beschwerden (rec) (M = 4.33; SD = .78), Schulfreude erleben aber viele Lernende nur eingeschränkt (M = 2.98; SD = .81). Bei der Berücksichtigung soziodemographischer Variablen wird ersichtlich, dass viele familiäre Faktoren (z. B. Anzahl der Geschwister, Familiensprache Deutsch, Erwerbssituation der Eltern) keine statistisch bedeutsamen Unterschiede hervorrufen. Großen Einfluss erzeugen hingegen die jeweiligen Bildungsabschlüsse der Eltern: Kinder von Akademikereltern besitzen eine deutlich höhere Erfolgszuversicht im Unterricht als Kinder, deren Eltern nicht die Hochschule besuchten (F = 6.01; p = .000). Weitere zentrale Befunde der Studie werden präsentiert, Limitationen und Implikationen der Studie für die Berücksichtigung schulischen Wohlbefindens diskutiert.  Zusammenfassung für das Programm Speziell in der Sekundarstufe, nicht zuletzt auch bedingt durch schulische Selektionsprozesse, wird häufig ein Absinken des Wohlbefindens sowie eine vermehrte negative Einstellung den Lehrpersonen gegenüber beobachtet (Bergmann & Eder, 1995). In der zu präsentierenden Studie wird daher untersucht, wie psychisches sowie physisches Wohlbefinden ausgeprägt sind und wie sie mit verschiedenen individuellen (u. a. Gender, Schulleistung), soziodemographischen (u. a. Familiensprache, elterliche Unterstützung) und schulischen Aspekten (Lehrerverhalten, Unterricht) zusammenhängen. An der Studie nahmen 1077 Schüler/innen (50 % weiblich) der 5. bis 13. Klassenstufe aus 14 Sekundarschulen teil (Durchschnittsalter 14 Jahre; SD = 2.07). Das schulische Wohlbefinden der Schüler/innen wurde angelehnt an Hascher (2004) erhoben und erfasst sieben Dimensionen. Daneben wurde u. a. die Unterrichtsqualität, das Lehrerverhalten und Aspekte des Schulklimas erfasst, wobei überwiegend standardisierte Instrumente zum Einsatz kamen (α zwischen .67 und .91). Es zeigt sich, dass in der Stichprobe insgesamt ein mittleres bis hohes schulisches Wohlbefinden vorliegt. Allerdings variieren die Werte der Teilkomponenten deutlich: So plagen die Schüler/innen zwar selten körperliche Beschwerden (rec) (M = 4.33; SD = .78), Schulfreude erleben aber viele Lernende nur eingeschränkt (M = 2.98; SD = .81). In der Präsentation werden weiter v. a. die Effekte der angeführten soziodemographischen Variablen diskutiert. Literaturangaben Eder, F. (1995). Das Befinden von Kindern und Jugendlichen in der Schule. Innsbruck: Studien-Verlag. Hascher, T. (2004). Wohlbefinden in der Schule. Münster: Waxmann. Stecher, L. (2000). Entwicklung der Lern- und Schulfreude im Übergang von der Kindheit zur Jugend. Welche Rolle spielt die Familienstruktur und die Qualität der Eltern-Kind-Beziehung? Zeitschrift für Soziologie der Erziehung und Sozialisation 20 (1), 70-88.
Keywords: Schulisches Wohlbefinden; Schule; Unterricht; Individuum; Eltern